Long-term outcomes of childhood sexual abuse: An umbrella review - Hailes, HP; Yu, R; Danese, A; Fazel, S (Elsevier, 2019)
Background: Although many meta-analyses have examined the association between childhood sexual abuse and subsequent outcomes, the scope, validity, and quality of this evidence has not been comprehensively assessed. We aimed to systematically review existing meta-analyses on a wide range of long-term psychiatric, psychosocial, and physical health outcomes of childhood sexual abuse, and evaluate the quality of the literature.